Isolation and Morphological Characterization of Bacteria Degrading on Soil Contaminated by Wasted Cooking Oil - Nurza, Imam Safir Alwan (MAXIMUS: Journal of Biological and Life Sciences, 2023)
Oil is used as an important component in human life as an energy source. The fried oil gives a delicious taste for consumption. However, the remaining cooking oil that has been cooked is discarded in the surrounding environment which is the cause of soil contamination by the oil. Thus, bioremediation is carried out to degrade contaminants with the ability of microorganisms or macroorganisms to become harmless compounds. The purpose of this research was to isolate and characterize the morphology of bacteria hydrocarbon-degrading from the environment or soil that had used cooking oil spills. The research method used was purposive sampling and descriptive qualitative. Purposive sampling is by determining where the sample to be taken has soil contaminated with used cooking oil and qualitative description is by describing the morphological characterization of the bacterial degrading isolates from the sample. The results of the research obtained that two bacterial isolates had a round shape, optically opaque, and flat edges. BCO-1 isolate has a brown color with a flat elevation and BCO-2 is white with a convex elevation. The bacteria degrading in BCO-1 isolates had a significant ability to degrade used cooking oil that was contaminated in the soil compared to BCO-2 isolates based on changes in the level of oil fluid.